When Do Donors Trust Recipient Country Systems? - Knack, Stephen (World Bank, Washington, DC, 2012)
The 2005 Paris Declaration on Aid Effectiveness sets targets for increased use by donors of recipient country systems for managing aid. The target is premised on a view that country systems are strengthened when donors trust recipients to manage aid funds, but undermined when donors manage aid through their own separate parallel systems. This study provides an analytical framework for understanding donors' decisions to trust or bypass country systems. Empirical tests are conducted using data from three OECD-DAC surveys designed to monitor progress toward Paris Declaration goals. Tests show that a donor's use of the recipient country's systems is positively related to: (1) the donor's share of aid provided to the recipient (a proxy for the donor's reputational stake in the country's development); (2) perceptions of corruption in the recipient country (a proxy for the trustworthiness or quality of the country's systems); and (3) public support for aid in the donor country (a proxy for the donor's risk tolerance). Findings are robust to corrections for potential sample selection, omitted variables or endogeneity bias.